Panbiogeographical analysis of Costa Rican freshwater fishes - Herrera Vásquez, Jonathan (2008)
Track analysis and Parsimony analysis of endemicity (PAE) were performed to analyze the distribution pattern of Costa Rican freshwater fishes. A basic matrix (presence/absence) was prepared using the distribution of 77 freshwater fish. The data were analyzed with CLIQUE software in order to find generalized tracks (cliques). Data also were analyzed with the software NONA and Winclada version 1.00.08 in order to perform the Parsimony Analysis of Endemicity (PAE). Fourteen equally probable cliques were found with 31 species in each and the intersection of the amount was selected as a generalized track dividing the country in two main zones: Atlantic slope from Matina to Lake Nicaragua and Pacific slope from the Coto River to the basin of the Tempisque River connected with some branches oriented to the central part of the country. PAE analysis found ten cladogram areas (72 steps, CI=0.45, RI=0.64), using the "strict consensus option" two grouping zones were identified: Atlantic slope and Pacific slope. Both PAE and Track Analysis show the division of the two slopes and the orientation of the generalized track suggests new biogeographical evidence on the influence of both old and new southern elements to explain the migrations of freshwater fish into Central America during two different geological events.